Didactic Lecture Versus Interactive Workshop for Continuing Pharmacy Education on Reproductive Health: A Randomized Controlled Trial. (September 2015) - Javadi, Mohammadreza; Kargar, Alireza; Gholami, Kheirollah; Hadjibabaie, Molouk; Rashidian, Arash; Torkamandi, Hassan; Sarayani, Amir
Pharmacists are routinely providing reproductive health counseling in community pharmacies, but studies have revealed significant deficits in their competencies. Therefore, continuing pharmacy education (CPE) could be utilized as a valuable modality to upgrade pharmacists' capabilities. A randomized controlled trial was designed to compare the efficacy of CPE meetings (lecture based vs. workshop based) on contraception and male sexual dysfunctions. Sixty pharmacists were recruited for each CPE meeting. Small group training using simulated patients was employed in the workshop-based CPE. Study outcomes were declarative/procedural knowledge, attitudes, and satisfaction of the participants. Data were collected pre-CPE, post-CPE, and 2 months afterward and were analyzed using repeated measure analysis of variance and Mann–Whitney U test. Results showed that lecture-based CPE was more successful in improving pharmacists' knowledge post-CPE ( p < .001). In contrast, a significant decrease was observed in the lecture-based group at follow-up ( p = .002), whereas the workshop-based group maintained their knowledge over time ( p = 1.00). Knowledge scores of both groups were significantly higher at follow-up in comparison with pre-CPE ( p < .01). No significant differences were observed regarding satisfaction and attitudes scores between groups. In conclusion, an interactive workshop might not be superior to lecture-based training for improving pharmacists' knowledge and attitudes in a 1-day CPE meeting.